Molecular characterization and antimicrobial susceptibility of human Brucella in Northeast China - Ma, Han-rui; Xu, Hui-jiao; Wang, Xin; Bu, Zhao-yang; Yao, Teng; Zheng, Zun-rong; Sun, Yang; Ji, Xue; Liu, Jun (Frontiers in Microbiology, 2023)
Brucella is a widespread and highly pathogenic bacteria that poses serious threats to public health and animal husbandry. In this study, 61 Brucella isolates were identified by abortus-melitensis-ovis-suis polymerase chain reaction and epidemic potential was clarified by multi-locus sequence analysis. Whole-genome sequencing (WGS) was performed and the antibiotic susceptibility of the Brucella strains against 13 antibiotics was detected with the use of E-test strips. The results showed that all of the isolates were Brucella melitensis ST8, group CC4 with little genetic variation and obvious geographical characteristics. All 61 Brucella isolates were sensitive to doxycycline, tetracycline, minocycline, levofloxacin, ciprofloxacin, gentamicin, and streptomycin, while 24.6%, 86.9%, 65.6%, 27.9%, 3.3%, and 1.6% were resistant to rifampin, azithromycin, cefepime, cefoperazone/sulbactam, cefotaxime, and meperidine/sulfamethoxazole, respectively. This is the first report of cephalosporin-resistant B. melitensis in China. The WGS results indicated that about 60% of the antibiotic resistance genes were associated with efflux pumps (mainly the resistance nodulation division family). Brucellosis is usually treated with antibiotics for several months, which can easily lead to the emergence of antibiotic resistance. To ensure the effectiveness and safety of antibiotics for treatment of brucellosis, continuous surveillance of antibiotic susceptibility is especially important.